2010
DOI: 10.1143/jjap.49.04df03
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Optical Response of InAlAs/InAs/InGaAs Pseudomorphic High Electron Mobility Transistors

Abstract: High-electron-mobility transistors with a pseudomorphically strained InAs channel (InAs-PHEMTs) have excellent electron transport properties and a high electron density, which are due to their large conduction band discontinuity. In this work, we show the dependence of optical response on drain-to-source voltage (V DS) for InAs-PHEMTs and clarify the physical mechanism for the response time. The experimental results can be explained successfully using two different lifetimes, one dominated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…We have been studying the physical properties of a phenomenon expressed in high electron mobility transistors (HEMTs) of the kind used in ultra-highspeed field effect transistors (FETs) [3][4][5]. Our previous research on inhibitors of carrier transport led us to propose fusing a high-speed device with a photo-responsive device [6].…”
Section: Introductionmentioning
confidence: 99%
“…We have been studying the physical properties of a phenomenon expressed in high electron mobility transistors (HEMTs) of the kind used in ultra-highspeed field effect transistors (FETs) [3][4][5]. Our previous research on inhibitors of carrier transport led us to propose fusing a high-speed device with a photo-responsive device [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have shown that InAlAs/InGaAs HEMTs have a high responsivity when they are used as optical receivers [5]. Recently, we have demonstrated that InAs-PHEMTs can operate as not only high-speed transistors but as ultra-high speed optical receivers [3][4][5][6].…”
mentioning
confidence: 99%